2021
DOI: 10.1001/jamaoncol.2021.1794
|View full text |Cite
|
Sign up to set email alerts
|

Association of COVID-19 mRNA Vaccine With Ipsilateral Axillary Lymph Node Reactivity on Imaging

Abstract: Intramuscular coronavirus 2019 (COVID-19) vaccinations could induce ipsilateral axillary lymph node reactivity that may be falsely attributed to malignant abnormality, prompting unwarranted interventions, or it may be falsely attributed to vaccination rather than cancer, potentially delaying cancer care. We aimed to investigate Moderna and Pfizer COVID-19 vaccine-related nodal reactivity on 18 F-flurodeoxyglocose (FDG) positron emission tomographic (PET)/computed tomographic (CT) scans. Letters E2JAMA Oncology

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 4 publications
4
51
1
Order By: Relevance
“…Unlike the literature [6], in our data, HLN detection rate was not influenced by oncological status, particularly by hematological disease and immunosuppressive/immunotherapy. In addition, differently from Adin et al, who observed a more common HLN detection rate after the Moderna vaccine (57%) than the Pfizer (15%) vaccine [9], the type of vaccination did not significantly impact on HLN detection; probably linked to the higher proportion (87%) of patients who received Pfizer vaccine in our sample.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Unlike the literature [6], in our data, HLN detection rate was not influenced by oncological status, particularly by hematological disease and immunosuppressive/immunotherapy. In addition, differently from Adin et al, who observed a more common HLN detection rate after the Moderna vaccine (57%) than the Pfizer (15%) vaccine [9], the type of vaccination did not significantly impact on HLN detection; probably linked to the higher proportion (87%) of patients who received Pfizer vaccine in our sample.…”
Section: Discussioncontrasting
confidence: 99%
“…Since mass COVID-19 vaccination started, several evidences of PET/CT findings have emerged in literature, which mainly consisted in clinical case reports [6][7][8][9][10].…”
Section: Discussionmentioning
confidence: 99%
“…Among the 728 vaccinated patients who underwent PET-CT scans in the aforementioned study, 113 (15.5%) were breast cancer patients [ 28 ]. A recently published study from the US (although with limited sample size and follow-up) also found that women might be more likely to develop reactive nodes following COVID-19 vaccination, with 7 out of 9 (78%) patients with lymphadenopathy (in a cohort of 68 vaccinated patients undergoing PET-CT scan for oncological indications) being female [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most common adverse reactions include pain at the injection site, headache, fatigue, myalgia, fever, and joint pain [2] . Less common side effects include lymphadenopathy or lymphadenitis in the ipsilateral axillary region [3] . Additionally, reactivation of the Gammaherpesvirinae subfamily, such as Epstein-Barr virus (EBV), and herpesvirus have been reported in case studies [4] , [5] , [6] .…”
Section: Introductionmentioning
confidence: 99%